PENGARUH PRODUKSI PERIKANAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI GORONTALO - Saputra, Excell Kurnia Febrian Eka; Mopangga, Herwin; Santoso, Ivan Rahmat (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023, 2023)
Good economic growth is an indicator to see the success of a region's development, good economic growth can be realized with an increase in all economic sectors. This study aims to determine the effect of fisheries production on economic growth in Gorontalo Province. This research uses a quantitative approach. The data used is secondary data obtained from the Central Statistics Agency (BPS) during the 2011-2020 time period and the unit of analysis is 5 districts and 1 city in Gorontalo Province. This study uses simple linear regression analysis of panel data with the Random Effects Model (REM) method.The results of this study indicate that Fisheries Production has a positive and significant effect on Economic Growth in Gorontalo Province during the 2011-2020 period. This means that every 1-year increase in fisheries production in the Regency / City is significantly able to increase economic growth in Gorontalo Province.